2019
DOI: 10.17261/pressacademia.2019.1164
|View full text |Cite
|
Sign up to set email alerts
|

The impact of digitalization on the audit profession: a review of Turkish independent audit firms

Abstract: Purpose -The aim of exploratory study is to increase the understanding of the effects digitalization has on the tools and working methods of the audit profession. Methodology -Websites of 235 audit firms authorized by POA (Public Oversight, Accounting and Auditing Standards Authority) were examined. In addition, transparency reports of 64 companies authorized for Public Interest Entity (PIE) Audit were investigated as well. The status of the services provided by the audit companies after the technological deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 3 publications
0
3
0
4
Order By: Relevance
“…Similarly, Adiloglu and Gungor (2019) aimed to better understand how digitization affects the instruments and procedures used by the audit profession in Turkey. It was found that only the Big Four make the required infrastructural and human resource investments in addition to offering these services.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, Adiloglu and Gungor (2019) aimed to better understand how digitization affects the instruments and procedures used by the audit profession in Turkey. It was found that only the Big Four make the required infrastructural and human resource investments in addition to offering these services.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Impacto de la digitalización La digitalización acelerada de la economía pone en tela de juicio el abandono previo de las conferencias de TI en las áreas especializadas de auditoría (Adiloglu & Gungor, 2019). Antes de adaptar los conceptos de formación y educación superior, se debe discutir la cuestión de qué efectos específicos podría tener la digitalización en la auditoría externa (Cipek & Ljutić, 2021).…”
Section: 2unclassified
“…Una solución sensata podría ser el uso de automatismos en combinación con un control final por parte del auditor o auditor interno. Adiloglu & Gungor (2019) dicen que es improbable que el auditor externo o el auditor interno sean prescindibles en tales tareas en el futuro previsible, ya que incluso los automatismos altamente desarrollados en el campo de la inteligencia artificial no son capaces de abstracción o creatividad humana. Además, incluso el software altamente desarrollado debe ser manejado por humanos que, por ejemplo, la existencia de varias facturas con el mismo número de factura es un signo de irregularidades en la contabilidad o que el riesgo de medidas de modelación de hechos es particularmente alto si las expectativas del analista no se cumplen.…”
Section: Automatización De Actividadesunclassified
See 1 more Smart Citation
“…Thus, there must be no denial of the need to embrace the shift to sophisticated technology, especially since more businesses are apt in setting foot in the new sphere. As a result, the professional practices and services rendered by audit companies will be altered (Adiloglu & Gungor, 2019). Lombardi et al (2014) claimed that the industry of auditing is one of the most influenced areas in technological innovations.…”
Section: Introductionmentioning
confidence: 99%